Technology Integration in Educating the Public about Law in the Digital Era - Desafa Putri, Ananda; Yudha Prayoga, Sandi (Yayasan Meira Visi Persada, 2024)
The objective of this research is to explore the integration of technology in educating society about law in the digital era. The research employs a juridical normative research method. Data sources include legislative regulations and policies related to the discussed legal issues. Indeed, advancements in information technology have fundamentally changed how humans live their daily lives. Information technology enables us to quickly create, modify, store, communicate, and disseminate information globally. In this context, legal awareness or individuals' understanding of laws and regulations becomes crucial. Society needs a strong understanding of their rights and obligations in facing new challenges arising in the digital era. High legal awareness helps create a civilized society and ensures effective law enforcement amidst evolving technological changes and social dynamics